DNA sequences near the site of reciprocal recombination between a c-myc oncogene and an immunoglobulin switch region. - Dunnick, W (1983)
The chromosomal translocations found in many B-cell tumors result in the joining of a c-myc oncogene with an immunoglobulin heavy chain switch region. This finding is striking because the natural function of switch regions is to mediate DNA rearrangements important to the maturation of immune responses. These normal switch rearrangements are probably mediated by specific enzymes. In this paper we report the isolation of the two reciprocal products of a recombination between a c-myc gene on murine chromosome 15 and an immunoglobulin switch region (S mu S gamma 2b) on chromosome 12. We have determined the sequences of these DNA molecules near the recombination sites and show that the recombination is nearly perfectly reciprocal, with a seven-nucleotide deletion. An examination of the sequences reported in this paper, and of sequences published by other authors, shows a correlation between the points of recombination for c-myc-S segment rearrangements and for normal heavy chain switches. We suggest that this correlation implies a role for switch recombination enzymes in creating substrates for the c-myc recombination. The c-myc gene also seems to share some limited homology to sequences thought to be important in heavy chain switching. Finally, we discuss a working model that accounts for some characteristics of c-myc-S segment recombinations. The model also suggests a mechanism for increased transcriptional activity of the rearranged c-myc oncogene in B-cell tumors.